Do inhaled corticosteroids protect against lung cancer in patients with COPD? A systematic review. Issue 1 (19th October 2016) - Raymakers, Adam J.N.; McCormick, Natalie; Marra, Carlo A.; Fitzgerald, J. Mark; Sin, Don; Lynd, Larry D.
ABSTRACT: Inhaled corticosteroids (ICS) are commonly prescribed to COPD patients, particularly those with more advanced stages of the disease. These patients are also at increased risk of lung cancer. A systematic review was undertaken to identify studies that examined the association between lung cancer risk and ICS therapy in COPD patients. The search strategy was created in MEDLINE and extended to EMBASE as well as other relevant databases. Both randomized controlled trials (RCTs) and observational studies were considered for inclusion. Studies were required to have incident lung cancer or deaths from lung cancer as an outcome in order to be included in the review. Six studies met the inclusion criteria. Two observational studies directly addressed the specific research. Four RCTs presented sufficient data to calculate the relative risk of lung cancer in COPD patients. None of the identified RCTs showed a statistically significant association of ICS use with lung cancer risk. Observational studies showed a protective effect from ICS use, particularly at high doses. Given the observational evidence and the low numbers of lung cancer events in the RCTs, these results may be prone to type II error. The observational studies dealt with very specific patient populations and exposure definitions, which might not have adequately captured the complex relationship between ICS exposure and lung cancer risk. Results from RCTs suggest no effect of ICS on the risk of lung cancer. However, results from observational studies suggest the potential that ICS may confer a protective effect, particularly at high doses.